2017
DOI: 10.1038/s41598-017-07508-x
|View full text |Cite
|
Sign up to set email alerts
|

Work stress, anthropometry, lung function, blood pressure, and blood-based biomarkers: a cross-sectional study of 43,593 French men and women

Abstract: Work stress is a risk factor for cardio-metabolic diseases, but few large-scale studies have examined the clinical profile of individuals with work stress. To address this limitation, we conducted a cross-sectional study including 43,593 working adults from a French population-based sample aged 18–72 years (the CONSTANCES cohort). According to the Effort-Reward Imbalance model, work stress was defined as an imbalance between perceived high efforts and low rewards at work. A standardized health examination incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 49 publications
(41 reference statements)
2
26
0
1
Order By: Relevance
“…Figure 4, the findings from large-scale population studies are consistent with the above described process and show that stress is linked to both increased systemic inflammation and coagulation/viscosity as indicated by higher platelet levels 77 and excess risk of pulmonary embolism. 29 Stress is also related to cardiac arrhythmia, 78 elevated ambulatory blood pressure 103 --a measure that is more sensitive to temporary elevations in blood pressure than clinic-assessed blood pressure --and increased alcohol use in men, 77,81,104 three further factors which may precipitate the rupture of vulnerable atherosclerotic plaque or the formation of blood clots. Studies that have used online diary (eDiary) assessments of emotions combined with portable devices that continuously monitor electrical activity of the heart have confirmed that stress often precedes arrhythmia episodes.…”
Section: Pathophysiological Changes Contributing To Triggeringsupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 4, the findings from large-scale population studies are consistent with the above described process and show that stress is linked to both increased systemic inflammation and coagulation/viscosity as indicated by higher platelet levels 77 and excess risk of pulmonary embolism. 29 Stress is also related to cardiac arrhythmia, 78 elevated ambulatory blood pressure 103 --a measure that is more sensitive to temporary elevations in blood pressure than clinic-assessed blood pressure --and increased alcohol use in men, 77,81,104 three further factors which may precipitate the rupture of vulnerable atherosclerotic plaque or the formation of blood clots. Studies that have used online diary (eDiary) assessments of emotions combined with portable devices that continuously monitor electrical activity of the heart have confirmed that stress often precedes arrhythmia episodes.…”
Section: Pathophysiological Changes Contributing To Triggeringsupporting
confidence: 77%
“…12,14 In contrast, there is no consistent evidence to demonstrate an association of stress with such major atherosclerosis risk factors as hypertension and LDL-cholesterol. [75][76][77][78] The mechanisms underlying the increased risk of developing cardiovascular disease among individuals with stress can also be indirect via lifestyle changes that accelerate atherosclerosis. For example, there is evidence to suggest that work-related stress is associated with reduced leisure-time physical activity.…”
Section: Plausible Pathophysiological Changes Accelerating Atherosclementioning
confidence: 99%
“…Although one study suggested that work stress does not influence serum lipid or glucose levels, several other studies have shown a link between components of the metabolic syndrome and work stress. For example, in one French cross‐sectional study consisting of 43 593 men and women, work stress, characterized by the effort‐reward imbalance model, was associated with significantly lower levels of high‐density lipoprotein cholesterol among men and a higher BMI in both men and women, even after adjusting for covariables, such as age, socioeconomic status, health‐related behaviors, and symptoms of depression . In another study from Germany, work stress, also characterized by the effort‐reward imbalance model, was associated with the metabolic syndrome, which was defined as the presence of at least 3 of the following 5 components: increased blood pressure, elevated triglycerides, low high‐density lipoprotein, increased fasting glucose, and central obesity.…”
Section: Potential Mechanisms For a Link Between Work Stress And Chdmentioning
confidence: 99%
“…Poor mental health conditions are associated with worse bladder cancer prognosis, and high job stress tended to be seen among not only blue‐collar workers but also white‐collar workers in Japan, which contrasts with the pattern seen in Western countries . Chronic job stress may trigger systemic inflammation and stimulate the immune system, which is reflected by increased levels of white blood cell counts . Besides, neutrophil‐to‐lymphocyte ratio in differential leukocyte counts is a biomarker of systematic inflammation response, and systematic reviews and meta‐analyses suggest that a poorer bladder cancer prognosis is associated with higher levels of neutrophil‐to‐lymphocyte ratio .…”
Section: Discussionmentioning
confidence: 99%